Desenvolvimento de uma intervenção com foco preventivo baseada na terapia cognitivo-comportamental e na psicologia positiva para atletas de futebol adolescentes - Lindern, Daniele (2016)
Young soccer athletes suffer pressure for high performance and face intense workout routines. These youth also have to deal with their own expectations toward their career as well as their family expectations. The fault routine of these soccer players is characterized by the sports practices and school tasks and, in many cases, they have few social interaction, besides of being physically distant from their family and hometown. The life of these youth may be influenced by many risk factors, at the same time protective factors may also be diminished. This dynamic justifies the need for preventive intervention programs focusing on social and coping skills. In this sense, this study - part of a Master Degree thesis- aimed to understand the meaning of soccer in the lives of young athletes from a Brazilian soccer club and to develop an intervention based on Cognitive-Behavioral Therapy and Positive Psychology for young soccer players of a football club in Brazil And was presented in two manuscripts. The design of the manuscript I was cross-qualitative, and individual semi structured interviews with four athletes from the soccer club were held, aiming to achieve athletes' perceptions in order To respect and attend their demands to develop the intervention. Data analysis was performed using Content Analysis. The results of the manuscript I point to the many adversities that these athletes go through to achieve the dream of being a soccer player. Thus, it is emphasized the important role of psychology in this context, that should value and reinforce, beyond the risk factors, the personal meanings that these youth attribute to their practice and role as soccer players. From the manuscript I results, an intervention was planned, which effects Were assessed and described in the second manuscript of this thesis. The manuscript II design was quasi-experimental with pre-and post-test. Twenty soccer athletes aged between 15 and 16 years, allocated in an experimental group (n=10) and control group (n=10) participants at the study. Manuscripts I and II included different participants. The intervention took place through eight meetings of 90 minutes each, once a week. The elements of the well-being of Positive Psychology, resilience, social skills, cognitive distortions and coping skills were the intervention focus. Participants answered the Inventory of Social Skills for Adolescents, Athletic Coping Skills Inventory, Screen for Child Anxiety Related Emotional Disorders, Life Satisfaction Global Scale and Positive and Negative Affect Scale for Adolescents pre and post-intervention. The control group didn't received any treatment. There was no significant difference between the experimental and control group pre and post intervention. However, the athletes of the experimental group showed significant difference in the coping skills “Under Pressure Performance”, “Trust” and “Freedom of Concerns”, and significant increase of the frequency of total score of social skills and of the ability to “Affective approach” after the intervention. The results of this study point to the importance of interventions that aim, the learning of other life skills beyond sports for these athletes, as promotion their mental health.